Perlindungan Hukum Terhadap Tenaga Kerja Indonesia di Saudi Arabia Perspektif Hukum Indonesia dan Saudi Arabia - Badruzzaman, Badruzzaman (UIN Sunan Kalijaga Yogyakarta, 2016)
In Indonesia, labor is one of the drivers of economic life and is a resource that is quite abundant. Economic conditions that are less attractive in their own country and incomes that are quite large and appear more attractive in destination countries have become triggers for international labor mobility. And the destination of most Indonesian workers is Saudi Arabia. As a developed country and a recipient of workers from Indonesia, it is not necessarily supported by progress in legal protection for migrant workers working in Saudi Arabia. Even though in the end Saudi Arabia was represented by the Ministry of Manpower and had issued Labor Laws and Regulations. This article is a library research approach that is used is normative-juridical. The authors compare the concept of legal protection for migrant workers in Saudi Arabia according to Indonesian Law and Saudi Arabian Law. Based on the results of the research that has been done, it can be concluded that Law Number 13 of 2003 concerning Manpower and Law Number 39 of 2004 concerning the Placement and Protection of Overseas Workers, as well as the King's Decree No. (A/91) Basic Law of Governance and in the Labor Law issued by the Ministry of Manpower of Saudi Arabia No. M/51. It is a form of guarantee that the Government of Indonesia and the Government of Saudi Arabia provide legal protection for Indonesian Migrant Workers working in Saudi Arabia. The similarities in the concept of legal protection for migrant workers between the governments of Indonesia and Saudi Arabia are both clearly stated in the laws and regulations of the two countries. The difference from the concept of legal protection for migrant workers lies in the handling process/field. In addition to the different legal basis, it is also difficult for Indonesian migrant workers to obtain definite legal protection for each case they experience. Saudi Arabia uses Islamic law or Sharia law as the legal basis so that the rules are set differently, so that the handling of the legal protection process for migrant workers is still weak.